Lack of effect of vitamin D3 supplementation in autism: a 20-week, placebo-controlled RCT. Issue 11 (16th June 2017) - Kerley, Conor P; Power, Clare; Gallagher, Louise; Coghlan, David
Abstract : Objectives: Data suggest a potential role for vitamin D in autism spectrum disorder (ASD). We wanted to assess the effect of vitamin D3 supplementation compared with placebo in children with ASD. Design: This was a double-blind, randomised, placebo-controlled trial. Setting: A paediatric outpatient centre at high latitude over the winter season in Dublin, Ireland (53°N). Patients: 42 children with ASD. Interventions: 2000 IU vitamin D3 supplementation or placebo daily for 20 weeks. Main outcome measures: Assessments were completed at baseline and after 20 weeks of supplementation. The primary outcome was the stereotypic behaviour subscale from the Aberrant Behaviour Checklist (ABC). Secondary exploratory outcomes included additional subscales from the ABC, the Social Responsiveness Scale and rating on the Developmental Disabilities—Children's Global Assessment Scale (DD-CGAS) as well as biochemical parameters of total vitamin D status (25-hydroxyvitamin D (25(OH)D)), immunity and systemic inflammation. Results: 38 children completed the trial. Baseline 25(OH)D was 54.2±19.7 nmol/L. Following vitamin D3 supplementation, there was a significant increase in 25(OH)D to 83.8 nmol/L (p=0.0016) but no effect on the primary endpoint. However, there was an improvement in self-care on DD-CGAS (p=0.02). In contrast, there was also a trend toward decreased inappropriate speech in the placebo group (p=0.08). Conclusion: Vitamin D supplementation had no effect on the primary outcome with limited and inconsistent effects in children with ASD. Considering the other promising data as well as the relative safety and cheapness of vitamin D supplementation, further trials are warranted. Trial registration: NCT02508922.